Radio tomographic imaging localization method based on the improved ellipse weight model - Li LI; Wei KE; Hengkuan XU; Kunliang YU; Yanli WANG (Tongxin xuebao)
As one of the main methods of device free localization (DFL), the radio tomographic imaging (RTI) method that can locate a target without attaching any devices has wide application prospects. To overcome the shortcoming of the existing ellipse weight model, based on the Fresnel diffraction theory an improved ellipse weight model was proposed to enhance the imaging quality of RTI and demonstrates the feasibility of this model. Meanwhile, a foreground detection algorithm based on the cross model was proposed to reduce the impact of background noises and pseudo-targets, thereby further improving the imaging quality. The indoor and outdoor experimental results verify that the imaging quality and the positioning accuracy of the proposed method are better than the existing RTI methods.